Association of Cadre's Knowledge with Age, Duration of Work, Education, and Employment on the Use of iPosyandu Application in Pasawahan, Purwakarta - Fedri Ruluwedrata Rinawan; Pratiwi Kusumastuti; Ariyati Mandiri; Rima Kusumah Dewi (Jurnal Ilmu Kesehatan Masyarakat, 2020)
Posyandu cadres are important people whose role in implementing posyandu, including registration, weighing, counseling, recording, and reporting. Currently, the cadre task in recording and reporting is still manual. Therefore, cadres must be supported by information technology to facilitate their work. iPosyandu application is an android-based or mobile application that is integrated and functioned for cadres in managing data. The application has been implemented at Posyandu to obtain data of infants, toddlers, and pregnant women, as well as child-bearing age women and couples (under development). This study aimed to determine the cadre's knowledge on the use of iPosyandu application at the posyandu, and its association with age, duration of work, education, and employment. The research method used cross-sectional approach. We used a purposive sampling technique. The sample size was 82 cadres in 6 villages in Pasawahan sub-district, Purwakarta Regency. Data collection was carried using questionnaire. Spearman correlation and Chi-square was used to identify the associations. The results was all cadres had good knowledge, and not associated with age, duration of work, education, and employment. This can be caused by the experience and implementation of the iPosyandu application during the last year. Other reasons were also identified such as easy access of media information, and the learning time. Good knowledge of cadres in using the application need to be maintained. Henceforth, further complementary research is needed to strengthen the knowledge by observing their skill under the umbrella of action research.